Thermal Design Optimization of Shell-and-Tube Heat Exchanger Liquid to Liquid to Minimize Cost using Combination Bell-Delaware Method and Genetic Algorithm - Setiawan, Reza; Hrdlička, František; Darmanto, Prihadi Setyo; Fahriani, Vera Pangni; Pertiwi, Suciani Rahma (Universitas Negeri Malang, 2020)
Shell-and-tube heat exchanger is designed to satisfy certain requirements such as heat transfer capability, allowable pressure drop and limitation of size. Beside such requirements, it is important to consider economical point of view to get the lowest total cost. In this study, computational program and optimization for thermal design shell-and-tube heat exchanger were built for liquid to liquid with no phase change process in four variables design parameters using Bell-Delaware method. The design variables were tube size, tube length, baffle cut to shell inside diameter ratio and central baffle spacing to shell inside diameter ratio. The genetic algorithm was used as optimization method to get lower solution for economical point of view. The results from two study cases show that the genetic algorithm got lower total cost from the original design. The total cost decreased 28.83% in first study case and 52.56% in second study case from the original design.